Hubungan Antara Kelekatan Orang Tua (Ibu) Terhadap Kecerdasan Emosi Pada Siswa Kelas XII Jurusan IPA SMAN 01 Tumijajar Kabupaten Tulang Bawang Barat - Qonita Iftinan; Junaidin (JURNAL PSIMAWA, 2021)
Attachment is a deep and long-lasting emotional bond that children form with their parents as a result of their interactions with them. These bonds can help children develop adaptively while also protecting them. Self-motivation, resilience in the face of failure, emotion management and deferred gratification, and mental state regulation are all examples of emotional intelligence. The purpose of this study was to see if there was a relationship between mothers' parental attachment and students' emotional intelligence. This study employed a quantitative correlation method. The sampling technique used purposive sampling with a total sample of 154 students in grade 12 majoring in science at SMAN 01 Tumijajar. All of the students still have mothers, with an error rate of 1%. According to the results, there is a relationship between mothers’ parental attachment and students’ emotional intelligence. The obtained correlation number of 0.219 with a significance value of 0.006<0.05 supports this claim. This number suggests that the mother's attachment variable and emotional intelligence are correlated, and that the relationship is positive. In other words, the stronger the mother's bond, the higher the emotional intelligence of the students, and vice versa.